Pelatihan Perawatan Payudara dengan Media Phantom Sebagai Treatment Keberhasilan ASI Ekslusif - Rahmah Hida Nurrizka; Dwi Mutia Wenny (Universitas Lancang Kuning, 2022)
One of the goals of the SDGs (Sustainable Development Goals) program is to end all forms of malnutrition with a strategic plan (strategic plan) to increase the percentage of babies less than 6 months who receive exclusive breastfeeding. Many mothers complain that their babies do not want to breastfeed. Usually, this is caused by technical factors such as the incoming nipple or the wrong nursing position. For this reason, efforts to educate pregnant women regarding exclusive breastfeeding are very important, followed by providing breast care training with Phantom Media. In increasing breastfeeding to infants, mothers need help and information and support to care for the breast during pregnancy to prepare for breastfeeding. From the results of the service, it can be seen that there are differences in the knowledge of pregnant women before and after being given education-related to exclusive breastfeeding and breast care with sig. (2-tailed) of 0.0 <0.05. From these results, it can be concluded health education can provide pregnant women with more health-related knowledge.